G05 Alterations in iron content in the brain of Huntington disease mutation carriers in comparison with healthy control subjects. (29th August 2012) - Sánchez-Castañeda, C; di Paola, M; Elifani, F; Maglione, V; di Pardo, A; Sabatini, U; Squitieri, F
Abstract : Background: It has been hypothesised that changes in iron content in the brain may be involved in the pathogenesis of Huntington Disease (HD). 1–5 T*2-weighted imaging may be a useful measure to study iron distribution in the brain since a strong linear correlation between chemically determined iron concentration and magnetic susceptibility has been established, specially for grey matter structures. 6 7 Increased iron content in the caudate, putamen and specially in the globus pallidus of HD patients and presymptomatic subjects has been described. 1–5 Aims: To investigate the potential spatial variations in T*2 signal in cerebral structure in Huntington disease mutation carriers. Methods: 77 mutation carriers (29 presymptomatic and 48 at early disease stages) and 73 age and gender matched controls underwent T*2 multiecho relaxometry on a 3 Tesla Siemens scanner (Abstract 12361-1 table 1). Six consecutive T*2- weighted gradient-echo whole-brain volumes were acquired using a segmented EPI sequence at different TEs: 6, 12, 20, 30, 45, 60 ms (TR: 5000, bandwidth: 1116 Hz/voxel, matrix size: 128 mm 3 ; voxel size: 1.8 mm 3 ). Image processing was performed combining FSL 4.0 and SPM8 running in Matlab 6.5. Artifacts in the susceptibility maps were avoided by using the first echo data to mask brain tissue. The statistical analysis of the susceptibility maps was carried by a two-sample t-test. The final results were corrected for multiple comparisons using a family wise error (FWE) rate correction set at p<0.05. Results: When compared with age and gender-matched control subjects, mutation carriers had increased iron levels in the globus pallidus/putamen bilaterally (p cluster: <0.001 left; <0.01 right; t: 7.41 left; 6.18 right). Furthermore, HD subjects had decreased iron content in occipital and posterior grey matter areas in comparison with control subjects (p cluster: <0.001; t: 6.65). Conclusions: The data suggest that iron alterations occur early in the HD process and have a role in the selective striatal degeneration underlying HD pathology. Prospective studies are needed to verify how increased iron levels are involved in HD pathogenesis. References: 1. Bartzokis G, Lu PH, Tishler TA, et al. Myelin breakdown and iron changes in Huntington's disease: pathogenesis and treatment implications. Neurochem Res 2007;32 :1655–64. 2. Bartzokis G, Cummings J, Perlman S, et al. Increased basal ganglia iron levels in Huntington disease. Arch Neurol 1999;56 :569–74. 3. Rosas HD, Chen YI, Doros G, et al. Alterations in brain transition metals in Huntington disease: an evolving and intricate story. Arch Neurol 2012. In press. 4. Sánchez-Castañeda C, Cherubini A, Elifani F, et al. Seeking huntington disease biomarkers by multimodal, cross-sectional basal ganglia imaging. Hum Brain Mapp 2012. In press. 5. Vymazal J, Klempír J, Jech R, et al. MR relaxometry in Huntington's disease: correlation between imaging, genetic and clinical parameters. J Neurol Sci 2007;263 :20–5. 6. Cherubini A, Péran P, Hagberg GE, et al. Characterisation of white matter fibre bundles with T2* relaxometry and diffusion tensor imaging. Magn Reson Med 2009b;61 :1066–72. 7. Langkammer C, Schweser F, Krebs N, et al. Quantitative susceptibility mapping (QSM) as a means to measure brain iron? A post mortem validation study. Neuroimage 2012. In press.